A High Throughput HPLC-MS/MS Method for Antihypertensive Drugs Determination in Plasma and Its Application on Pharmacokinetic Interaction Study with Shuxuetong Injection in Rats. (6th August 2019) - Wei, Juan; Ma, Wenjuan; Yao, Guangzhe; Jia, Qi; Cheng, Xuejing; Ouyang, Huizi; Chang, Yanxu; Chen, Xiaopeng; He, Jun
Abstract : A high-throughput HPLC-MS/MS method was developed and validated for the determination of four antihypertensive drugs including metoprolol tartrate, hydrochlorothiazide, nifedipine, and valsartan in rat plasma. The Sprague-Dawley rats were randomly divided into three groups: A Group: gastric-administration of metoprolol tartrate, hydrochlorothiazide, nifedipine, or valsartan; B Group: a single intravenous injection of SXT, then dosing as the A group; C Group: daily injection of SXT through the tail vein for 8 consecutive days and dosing as the A group on the eighth day. For metoprolol tartrate and valsartan, blood samples were collected before administration and at time points 0.03, 0.08, 0.17, 0.25, 0.5, 1, 2, 4, 6, 8, 10, 12, and 24 h from the fossa orbitalis vein. For hydrochlorothiazide and nifedipine, the time points were 0, 0.08, 0.17, 0.25, 0.5, 0.75, 1, 2, 4, 6, 8, 10, 12, and 24 h. The plasma samples containing different individual antihypertensive drug were mixed and prepared by protein precipitation with methanol. The chromatographic separation was performed on an Agilent Eclipse Plus C18 column (2.1 mm×100 mm, 3.5 μ m) using gradient elution with mobile phase consisting of acetonitrile and water (containing 0.1% formic acid). The flow rate was 0.3 mL/min. The detection was accomplished on a tandem mass spectrometer with an electrospray ionization (ESI) source by multiple reaction monitoring (MRM) in both positive and negative modes. The method was successfully applied to a pharmacokinetic interaction study of Shuxuetong injection on the antihypertensive drugs. The results suggested that SXT could increase the total amount of metoprolol tartrate and nifedipine in plasma and showed little influence on the pharmacokinetic behaviors of hydrochlorothiazide and valsartan.